Instagram an Intimate Medium for Social Connectivity between Celebrity and Fans – A Textual Analysis: Exploring Instagram as a Platform for Fan Engagement and Intimate Connections (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Instagram a mobile photo-sharing application and service that allows users to share a photos, videos, personal views, thoughts, ideas and opinions, and comments of their lives with a large quantity of audience in a matter of seconds. The celebrities create a good relationship with their fans through their posts published on Instagram. The purpose of this research paper is to find fan engagement and intimate relationship between the celebrities and their fans. For this research paper we analyzed 50 Instagram posts of top three bollywood celebrity—Salman khan, Shahrukh khan and Aamir khan—to find which categories of posts engage fans. It also investigated the intimate relationship with their fans through their comments.